PENGENDALIAN PERILAKU MENYIMPANG OLEH GURU DALAM PROSES PEMBELAJARAN KELAS XI SMK BINA UTAMA SANGGAU - Sari, Yunia; Budjang A, Gusti; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problemin this study was how to of teachers in the learning and teaching process for XI  grade students at the SMK Bina utama in Sanggau ? Based on the formulation of the problem, the sub-problem was formulated as follows: how to control the prevention and suppression by teachers in the learning process for students of class XI at the Bina Utama in Sanggau. This study used qualitative inquiry with descriptive methods. The data collection tool used observation guidelines, guesswork guides, and documentation studies. The decision showed that 1. Preventive social control carried out by the teacher before starting the learning process and teaching the teacher to guide, direct, and invite students not to be deviant in school both in the learning process in the classroom and in the school environment. 2. Oppressive social control carried out by the teacher when looking for students who are devious when learning activities in the classroom teachers give direct reprimands 3. Social control is curative by the teacher by giving penalties or sanctions to students who are deviant so students realize mistakes and do not repeat the same action to give the impression of prevention to students who are deviant and other students.  Keywords: Deviant Behavior Social Control, Students,Teacher,